2010
DOI: 10.1053/j.gastro.2009.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L Inactivates Human Trypsinogen, Whereas Cathepsin L-Deletion Reduces the Severity of Pancreatitis in Mice

Abstract: Background & Aims-Acute pancreatitis is characterized by an activation cascade of digestive enzymes in the pancreas. The first of these, trypsinogen, can be converted to active trypsin by the peptidase cathepsin B (CTSB). We investigated whether cathepsin L (CTSL), the second most abundant lysosomal cysteine proteinase, can also process trypsinogen to active trypsin and has a role in pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
99
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 30 publications
4
99
0
Order By: Relevance
“…To this end, we measured (51) the effects of starvation and pancreatitis on the processing and activities of two major lysosomal hydrolases, cathepsins (Cat) B and L. Both cathepsins are relevant for pancreatitis: CatB proteolytically converts trypsinogen to trypsin (32,75,79), whereas CatL degrades both trypsinogen and trypsin (51,88). We found that starvation has little effect on pancreatic activities of CatB and CatL and their processing into fully mature, active forms.…”
Section: Lysosomal Dysfunction and Impaired Autophagy In Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, we measured (51) the effects of starvation and pancreatitis on the processing and activities of two major lysosomal hydrolases, cathepsins (Cat) B and L. Both cathepsins are relevant for pancreatitis: CatB proteolytically converts trypsinogen to trypsin (32,75,79), whereas CatL degrades both trypsinogen and trypsin (51,88). We found that starvation has little effect on pancreatic activities of CatB and CatL and their processing into fully mature, active forms.…”
Section: Lysosomal Dysfunction and Impaired Autophagy In Pancreatitismentioning
confidence: 99%
“…7). Indeed, we (51) and the groups of Markus Lerch and Walter Hallangk (32,88) showed that these cathepsins have opposite roles in trypsin accumulation: whereas CatB converts trypsinogen to trypsin, CatL does not activate trypsinogen but, on the contrary, degrades both trypsin and trypsinogen. We propose (51) that in pancreatitis, because of defective lysosomal function, CatL activity is not sufficient to degrade activated proteases (such as trypsinogen), resulting in trypsin accumulation in autophagic 2706 GUKOVSKY ET AL.…”
Section: Lysosomal Dysfunction and Impaired Autophagy In Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the lysosomal hydrolase cathepsin-L degrades trypsinogen to an inactive form of trypsin thus providing protection against premature zymogen activation. Paradoxically, when cathepsin-L is genetically deleted there is also a switch from acinar cell necrosis to apoptosis with reduced severity of disease (Wartmann et al, 2010). This indicates that cathepsin L may be involved in additional pathways which contribute to pancreatitis.…”
Section: Role Of Premature Trypsinogen Activationmentioning
confidence: 99%
“…The lysosomal hydrolase cathepsin-B prematurely converts the digestive zymogen, trypsinogen, to its active form, trypsin (Figarella et al, 1988;Gorelick and Matovcik, 1995;Lerch et al, 1995;Wartmann et al, 2010). This conversion requires an acidic pH and cathepsin-B activates trypsinogen in a pH dependent manner (Kukor et al, 2002).…”
Section: Role Of Premature Trypsinogen Activationmentioning
confidence: 99%